2002
DOI: 10.1063/1.1447513
|View full text |Cite
|
Sign up to set email alerts
|

Study on the preparation techniques and properties of bonded magnetostrictive materials

Abstract: The preparation and measurement of the magnetoelastic properties of bonded Terfenol-D and Pr0.15Tb0.3Dy0.55Fe2 composites are reported. The experiments were carried out in various conditions, including compaction pressure and binder proportion in order to optimize the preparation method. The typical conditions are with the compaction pressure between 48 and 80 MPa and a weight ratio of binder to powder of 4:100. Large magnetostrictions of 1186×10−6 at 450 KA/m for the Terfenol-D composite with an applied compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The epoxy/Tb 1−x Pr x (Fe 0.4 Co 0.6 ) 1.9 composites for x = 0.9-1.0 all have a high magnetostriction of about 500 ppm at 6 kOe, which is about the same as that of the Terfenol-D composite reported by Sandlund et al [10], smaller than the reported values in Refs. [19,20]. But the epoxy/Pr(Fe 0.4 Co 0.6 ) 1.9 composite free of high-cost heavy rare earth Tb and Dy, should have an economic predominance than Terfenol-D composite, making it a promising magnetostrictive composite material for application.…”
Section: Resultsmentioning
confidence: 98%
“…The epoxy/Tb 1−x Pr x (Fe 0.4 Co 0.6 ) 1.9 composites for x = 0.9-1.0 all have a high magnetostriction of about 500 ppm at 6 kOe, which is about the same as that of the Terfenol-D composite reported by Sandlund et al [10], smaller than the reported values in Refs. [19,20]. But the epoxy/Pr(Fe 0.4 Co 0.6 ) 1.9 composite free of high-cost heavy rare earth Tb and Dy, should have an economic predominance than Terfenol-D composite, making it a promising magnetostrictive composite material for application.…”
Section: Resultsmentioning
confidence: 98%
“…The composite samples were prepared by crushed the melt-spun ribbons annealed at 773 K Table 1 The magnetization, coercivity and magnetostriction of Pr 0. 3 into powders and mixed with a phenol-type binder with the weight proportion of binder to powders of 4:100 [17]. The mixed powders were compacted under pressure of 80 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…This discovery opened the era of technical applications for the large magnetoelasticity of rare earth metals. Since then, much research has been done to improve the magnetostriction and magnetic properties of this commercial compound to make it more suitable for applications [2][3][4][5][6][7]. Many researchers have paid attention to prepare the oriented Tb 0.3 Dy 0.7 Fe 2 alloy and substitute other atoms for Fe in Tb 0.3 Dy 0.7 Fe 2 alloy [8][9][10].…”
Section: Introductionmentioning
confidence: 99%